(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2023)
In world linguistics, special attention is paid to the study of the semantics of linguistic units based on a cognitive, psycholinguistic approach. Based on psycholinguistic analysis, the relationship between language and speech, language and thinking, the codification of thinking through linguistic units, and the complete projection of thought in the mind of the listener are determined. The psycholinguistic approach is practical in analyzing issues of the mechanism of speech, worldview, processes of reflecting information about existence in the linguistic consciousness, mastering the meaning of words and retaining a concept in the memory of a language; the perception of the signs of an object, event, the formation of a lexeme as a seme, as well as clarifying the relationship between form and content in understanding lexical meaning.